Transformation in the photovoltaics industry in Australia, Germany and Japan: Comparison of actors, knowledge, institutions and markets - Marinova, Dora; Balaguer, A. (2009)
The paper analyses the evolution of the photovoltaics industry in Australia, Germany and Japan from a comparative policy perspective. It uses a sectoral innovation system framework to discuss the way the three countries have approached the development of knowledge and new technologies, the actors in the sector and the interactions between them, the role of institutions and availability of funding as well as the development of markets for photovoltaics. It outlines the different paths that the countries have adopted for the process of transition from niche to mass production. The findings show that various national players have specialised in different activities, with the institutions' building block being a key determinant for success or otherwise. In the case of Australia, it is also the least developed area which ultimately exposes the country to losing its innovation benefits. © 2008 Elsevier Ltd. All rights reserved.